Clubroot Disease Stimulates Early Steps of Phloem Differentiation and Recruits SWEET Sucrose Transporters within Developing Galls - Walerowski, P; Gundel, A; Yahaya, N; Truman, W; Sobczak, M; Olszak, M; Rolfe, S; Borisjuk, L; Malinowski, R (Amer Soc Plant Biologists, 2024)
Indexed by WOS